OC-108 Improving the diagnosis of pancreaticobiliary malignancy by the detection of minichromosome maintenance protein 5 in biliary brushings. (22nd June 2015) - Keane, MG; Huggett, MT; Johnson, GJ; Chapman, MH; Webster, GJ; Thorburn, D; MacKay, J; Pereira, SP
Abstract : Introduction: Biliary brush cytology is the standard method of evaluating a biliary stricture but has a low sensitivity for the detection of malignancy. Minichromosome maintenance (Mcm) replication proteins (Mcm 2–7) are raised in a number of cancers, where the active cycling of malignant cells results in the expression of these licensing proteins on the epithelial surface of the tumour. In pancreaticobiliary malignancies Mcm proteins are dysregulated in the epithelial lining of the bile ducts and in bile samples taken from patients with malignant pancreaticobiliary disease. The aim of this study was to evaluate an automated immunoflurometric assay of Mcm5 as a marker of malignancy in patients with indeterminate biliary strictures. Method: Biliary brush samples were collected prospectively at endoscopic retrograde cholangiopancreatography from patients with an indeterminate biliary stricture. Following sampling the brush was placed in a buffer solution, agitated and frozen to –80 o C. On defrosting the sample was placed in a microtitre plate strip of 8 wells coated with a purified mouse monoclonal antibody to Mcm5 and incubated for 2 h. The colour intensity was measured using a plate reader and a cut-off of 1.2 was used to indicate a positive result. Patients also underwent brush cytology and/or biliary biopsy as part of standard practice. Results: 75 patients were included in the study; median age was 65 years (range 20–94) and 68% (51/75) were male. Mcm5 levels in biliary brush samples were significantly more sensitive than brush cytology (89% vs. 18%; P = < 0.05) for the detection of malignancy in patients with an indeterminate stricture. The specificity, PPV and NPV of the Mcm5 assay were 96%, 98% and 84% respectively. Conclusion: Mcm5 from biliary brush cytology determined by a simple automated test is a more sensitive indicator of pancreaticobiliary malignancy than routine brush cytology. Disclosure of interest: None Declared.